Proinflammatory Cytokines Predict Brain Metabolite Concentrations in the Anterior Cingulate Cortex of Patients With Bipolar Disorder - Poletti, Sara; Mazza, Mario Gennaro; Vai, Benedetta; Lorenzi, Cristina; Colombo, Cristina; Benedetti, Francesco (Frontiers in Psychiatry, 2020)
Bipolar disorder (BD) is a severe psychiatric illness characterised by abnormalities in the immune/inflammatory function and in brain metabolism. Evidences suggest that inflammation may affect the levels of brain metabolites as measured by single proton magnetic resonance spectroscopy (1H-MRS). The aim of the study was to investigate whether a wide panel of inflammatory markers (i.e. cytokines, chemokines, and growth factors) can predict brain metabolites concentrations of glutamate, myo-inositol, N-acetylaspartate, and glutathione in a sample of 63 bipolar patients and 49 healthy controls. Three cytokines influenced brain metabolites concentrations: IL-9 positively predicts glutamate, IL-1β positively predicts Myo-Inositol while CCL5 positively predict N-acetylaspartate concentrations. Furthermore, patients showed higher concentrations of glutamate, Myo-Inositol, and glutathione and lower concentrations of N-acetylaspartate in respect to healthy controls. Our results confirm that inflammation in BD alters brain metabolism, through mechanisms possibly including the production of reactive oxygen species and glia activation.